Unlocking the Value of Waqf Assets via Islamic Real Estate Investment Trusts (Islamic REIT): A Deliberation on the Preliminary Framework - Sulaiman, Syahnaz; Hasan, Aznan; Adham, Khairul Akmaliah (Universiti Sains Islam Malaysia, 2019)
Insufficient fund to develop waqf properties remains as the main challenge and concern faced by the majority of waqf administrators in Malaysia. Thus, this paper aims to explore the potential of one of the Islamic capital market instruments, specifically Islamic Real Estate Investment Trusts (Islamic REIT), to unlock the value of underdeveloped and abandoned waqf properties through asset unitisation into share units in raising the capital for waqf development. A preliminary conceptual framework of REIT waqf is proposed. This study employed a qualitative research designed through the use of document analysis of classical Islamic books, Islamic ruling (fatwa), journal articles, books, online resources, and policy documents as well as interviews with waqf stakeholders. The characteristics of both waqf and Islamic REIT were analysed in order to determine the feasibility of the establishment of REIT waqf. Based on this study, a number of emergent major themes and sub-themes contributing towards the development of preliminary framework of REIT waqf were identified. On the whole, the idea of REIT waqf is still at its nascent stage. The findings demonstrate that despite several obstacles, Islamic REIT structure is viable to be advanced as a future framework to develop waqf properties provided that necessary measures are undertaken in order to address few legal and administrative issues.